Design and Construction of Liquid Soap Stirrer Made from Used Cooking Oil - Muhammad Imam Al Hakim; Ainun Rohanah; Lukman Adlin Harahap (Universitas Sumatera Utara, 2016)
The process in making liquid soap from used cooking oil is an interesting thing to know. This research was held to design, construct, test, and analyze economic value of liquid soap stirrer made from used cooking oil. The parameters observed were water content, free fatty acid (FFA), alcohol insoluble part, effective capacity, yield, and economic analysis. Based on this research, it was summerized that effective capacity of this equipment was 20,26 l/hr. Yield percentage was 97,8%. Basic cost for the first to fifth year were Rp 735,95/l, Rp 738,08/l, Rp 738,38/l, Rp 739,76/l and Rp 741,24/l. Respectively break event point was 440,53 l/year. Net present value with 7,5% rate was Rp 378.115.195 and internal rate of return was 48,36%. Keywords: liquid soap, used oil cook, effective capacity, yield, economic analysis